Analisis Pendapatan Usahatani Padi Sawah Di Subak Gubug 1, Tempek Pesaji, Desa Sudimara, Kecamatan Tabanan, Kabupaten Tabanan - Utami, Ni Made Astuti Wahyu; Wiguna , I Made Ananda; Sudana, Si Nyoman (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2025)
This study aims to determine the income level of farmers in rice farming in Subak Gubug 1, Tempek Pesaji, Sudimara Village, Tabanan District, Tabanan Regency. The data analysis used is descriptive data analysis. The results of the study show that the average income per hectare is Rp 9,593,297, with an average production of 3,279 kg, a selling price of Rp 5,000, variable costs of Rp 6,542,298, and fixed costs of Rp 259,405. Therefore, the total average production cost per hectare is Rp 6,801,703. Overall, the analysis results indicate that despite significant costs in the production process, the farmers still earn a positive income, which amounts to Rp 205,775,667. This indicates that the production activities provide a fairly good profit for the farmers.